Bilimbi (Averrhoa bilimbi L.) Leaf Extract Cream: Formulation and Efficacy in Accelerating Wound Healing in Male White Mice - Suena, Ni Made Dharma Shantini; Nayaka, Ni Made Dwi Mara Widyani; Wardani, I Gusti Agung Ayu Kusuma; Antari, Ni Putu Udayana (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2024)
Bilimbi (Averrhoa bilimbi L.) is known for its wound-healing potential due to its flavonoids, saponins, triterpenoids, and tannins. This study aims to develop a practical and stable dosage form of Bilimbi leaf extract, specifically a cream, and evaluate its efficacy as a wound-healing agent. Bilimbi leaf extract at 2% concentration was formulated into a cream with two variations of triethanolamine concentration as an emulsifier, F1 (2%) and F2 (4%). Data were collected through observation and measurement scales during the cream formulation stage. The effectiveness of the cream as a cut wound healer was assessed using a randomized control group pre-test and post-test design. Physical properties, including organoleptic properties, homogeneity, pH, and mechanical stability, were observed, and spreadability was measured. Both formulations met the criteria for creams with good physical quality and effectively reduced the wound length to 0 cm within the 7-day observation period. In contrast, in the control group, wounds still appeared to be 0.4-1 cm in size. In conclusion, the findings in this study indicate that the cream containing 2% Bilimbi leaf extract (Averrhoa bilimbi L.) has favorable physical characteristics and effectively heals incision wounds in male white mice. This formulation shows promise for further development regarding efficacy, safety, stability, and market acceptability.